Content Analysis of the Excellence of Employee Performance: a Study of the Employer branding Models - Syal, Ginni (The journal of contemporary issues in business and government, 2021)
Purpose – Review of literature provides number of models highlighting the perception of potential employees in context with employer branding. However, these models lack empirical investigation in different industries like insurance, tourism & travel, hospitality and banks. These frameworks have highlighted the perception of employers towards positioning their organisation image in the mind of potential employees.Six Online databases, namely, Emerald, JSTOR, Sage Publications, Science Direct, Springer Link and Taylor & Francis have been surfed to list the articles with title “Employer Branding” or with the title “Employer Attractiveness” and the total listed articles from databases of Taylor & Francis, Emerald, Springer Link, JSTOR, Science Direct and Sage Publications respectively have been thoroughly reviewed. The majority of studies on “Employer Branding” and on “Employer Attractiveness” have been carried out in different countries of the world that is in US, UK, China, Portugal, Netherlands, and in different service industries like hotels, banking, aviation and telecom sector. In theoretical terms, the researchers have remarked in their studies that employer branding terminology can be a strong basis for attracting the new talent and prospective candidate for the right job at right time in right place in various service industries. However, the focus has to be shifted in studying the employer branding terminology from current employee perspective.The study has provided basis for applying the models in different industries with the theoretical support. Future research should seek to give empirical evidence regarding the congruence between employer branding and employee performance. The conceptualized models can also be empirical investigated and may be employed in different industries to study the influence of various parameters on the service employees. The results from review of literature presented here should lead analysts to recognize that measuring and strategically managing employer branding may in fact become the most important managerial activity for driving organizational performance among current employees.The paper discusses the similarity and differences in the two models by [1]on employer branding from the perception of current employees towards their present organisation. The study provides a unique opportunity to understand the two models and their applicability in the banking industry. Moreover, these two models and its various perspectives were found to be more suitable and apt for the banking industry.